Maternal and neonatal complications between post-COVID pregnant patient and normal patient: a tertiary care hospital-based comparative study - George, Preetha; George, Anu Anna; Anaz, Meera; Soman, Annie (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: As the COVID-19 pandemic evolved the complications associated with acute infection have been well described. However, in the post-pandemic era, we must dwell on the obstetric sequelae of these infections. This study investigated the maternal and neonatal outcomes in post-COVID patients compared to normal pregnant women. Methods: A prospective cohort study was designed where women who had a COVID-19 infection during pregnancy were compared with concomitant pregnant women without a COVID-19 diagnosis. Women were followed up from enrolment in the outpatient department until one-week post-partum, and data were collected. Results: In this study, 201 women were included and divided into two groups. The women who had a COVID-19 infection during pregnancy had a significantly higher incidence of gestational diabetes mellitus (OR 3.6, 95% CI 1.0-12.6). There was also a significantly higher incidence of adverse perinatal complications (OR 1.5, 95% CI 1.1-2.0) particularly an increased rate of preterm delivery (OR 3.4, 95% CI 1.3-8.7) compared to the women who did not have a COVID-19 infection during pregnancy. Moreover, no significant differences existed in the measured outcomes when comparing women infected in the second trimester, to those infected in the third trimester. Conclusions: The development of complications such as preterm delivery and gestational diabetes mellitus among women after a COVID-19 infection during pregnancy underscores the necessity for close monitoring of such patients and the promotion of strategies to prevent infection.